2016
DOI: 10.1118/1.4948683
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of stopping power calibration with dual‐energy CT and single‐energy CT in proton therapy treatment planning

Abstract: DECT-based proton treatment planning in a commercial treatment planning system was successfully demonstrated for the first time. DECT is an attractive imaging modality for proton therapy treatment planning owing to its ability to characterize density and chemical composition of patient tissues. SECT and DECT scans of a phantom of known composition have been used to demonstrate the dosimetric advantages obtainable in proton therapy treatment planning with DECT over the current approach based on SECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 35 publications
1
94
0
Order By: Relevance
“…Due to comparable dose differences in the polymer and the anthropomorphic phantom, the authors transferred the results derived from the reference Catphan phantom to the Rando phantom for which a reference SPR dataset was not available (Section 3.D.). Based on these evaluations, the authors suggest clinical applicability and improved SPR accuracy of DECT for clinical treatment plans (“This suggests that the results obtained with the Catphan are a reasonable representation of potential advantages of DECT over SECT‐based clinical IMPT treatment planning”, last sentence in discussion).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Due to comparable dose differences in the polymer and the anthropomorphic phantom, the authors transferred the results derived from the reference Catphan phantom to the Rando phantom for which a reference SPR dataset was not available (Section 3.D.). Based on these evaluations, the authors suggest clinical applicability and improved SPR accuracy of DECT for clinical treatment plans (“This suggests that the results obtained with the Catphan are a reasonable representation of potential advantages of DECT over SECT‐based clinical IMPT treatment planning”, last sentence in discussion).…”
mentioning
confidence: 98%
“…A dosimetric comparison of proton treatment planning based on single‐energy CT (SECT) and dual‐energy CT (DECT) was recently published by Zhu and Penfold in Medical Physics . In this study, the polymer phantom Catphan Module 404 (The Phantom Laboratory, Salem, NY, USA) of known material composition was used to demonstrate an improved accuracy of dose calculation using DECT instead of SECT.…”
mentioning
confidence: 99%
“…In fact recent publications are showing promise for proton beam range calculation uncertainties to be in the order of 1% error with the use of dual energy CT (DECT). 35,36,37 A potential initial workflow in MRPT would then be to register daily MR images back to the original planning CT dataset. This would accurately account for any patient anatomy changes, provided that there is confidence in the deformable image registration process for the given anatomical site.…”
Section: A Mri-only Proton Therapy Planningmentioning
confidence: 99%
“…They confirmed a higher accuracy for DECT in their surrogate patients using a pencil beam algorithm. Zhu et al confirmed in a phantom the dosimetric advantages in proton therapy treatment planning with DECT over the current approach based on SECT [85]. Whether this is clinically relevant needs to be investigated in future.…”
Section: Applicationsmentioning
confidence: 99%